Throughout Seven Elements of Communication of Language on Martin Luther King’s Speech: A Discourse Analysis - Siti Maisyaroh Jumiati (JELITA, 2022)
Throughout the 17th to 18th centuries, slavery was practiced throughout the European colonies of America. Until the passage of the 13th Amendment to the United States Constitution in 1865, slavery in the United States was legal. Under the law, enslaved people are treated as property and can be bought, sold, or given away. Slavery lasted in about half of the states of the United States until 1865. Our aim with this paper was to review a little about slavery that took place in the United States and freed slaves with the passage of the Amendments to the United States Constitution which was delivered at Martin Luther King’s speech. The researcher analyzed using qualitative descriptive approach. The researcher found that there are macro functions in the speech delivered by King on August 28, 1963. We discussed there are seven elements of communication of language, namely the addressed, the addressee, the channel, the message form, the topic, the code, and the settings. In conclusion is the addresser is Martin Luther King, the addressee is 250.000 people, the channel is RARE FACTS, the message form is “I Have a Dream” was born from the unrest of Martin Luther King, a black man who was familiar with racial discrimination since childhood. As a fighter for equality, he is no stranger to challenges from white citizens or the government. But his speech that afternoon, managed to make about 250,000 people who gathered at the Lincoln Memorial amazed and burned with enthusiasm. In the speech, Luther King touched on issues of unemployment, racial, social justice, civil rights, gender equality between whites and blacks, and hopes for the repeal of laws and policies that support segregation based on race. The whole world then remembered the “I Have a Dream” speech as Martin Luther King's personal vision that had a huge impact on many people, the topic is I Have a Dream, the code is American English and the setting is on August 28, 1963 at the Lincoln Memorial, Washington DC. Solemn and calm.